1986
DOI: 10.1073/pnas.83.19.7467
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor type alpha stimulates human endothelial cells to produce granulocyte/macrophage colony-stimulating factor.

Abstract: Tumor necrosis factor type a (TNF-a) is produced by monocytes and has been purified, sequenced, and cloned from the HL-60 cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
154
1
3

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(167 citation statements)
references
References 36 publications
9
154
1
3
Order By: Relevance
“…[37][38][39][40][41][42][43][44][45][46][47] The relationship between the production of these cytokines and the functional ability of EC to support hematopoiesis may help in understanding the role played by these cells in the ontogeny of the hematopoietic system as EC are intimately associated with embryonic hematopoiesis and may be involved in the development of embryonic progenitors. 52,53 EC are also part of the bone marrow stromal microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40][41][42][43][44][45][46][47] The relationship between the production of these cytokines and the functional ability of EC to support hematopoiesis may help in understanding the role played by these cells in the ontogeny of the hematopoietic system as EC are intimately associated with embryonic hematopoiesis and may be involved in the development of embryonic progenitors. 52,53 EC are also part of the bone marrow stromal microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46][47] The functional importance of this production remains to be fully appreciated. As a direct relevant application, EC may for instance offer an improved alternative to unfractionated stroma cells as a source of feeder cells in bioreactors devised for ex vivo expansion of hematopoietic progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…So far, GM-CSF and G-CSF are known to be secreted by IL-stimulated ECs [5]. Other endothelial factors propagating progenitor expansion include stem cell factor (SCF) [6], leukemia inhibitory factor (LIF) [7] and IL-6 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we demonstrated that ECs stimulated by TNF-a induced the generation of dendritic cells from CD34 1 cells for more than 6 wk [3]. ILs, on the other hand, can also induce the proliferation of hematopoietic and myeloid progenitors [4].So far, GM-CSF and G-CSF are known to be secreted by IL-stimulated ECs [5]. Other endothelial factors propagating progenitor expansion include stem cell factor (SCF) [6] …”
mentioning
confidence: 99%
“…Second passage HUVEC were grown to confluence using culture :onditions previously described [25] in duplicate gelatin-coated 96 well )lares. After stimulation with cytokines, the supernatants were removed ?ore each plate and assayed for GM-CSF by ELISA activity as previmsly described [26].…”
Section: '1 Elisa Of Huvecmentioning
confidence: 99%